Identification of point mutations in Glucose-6-Phosphate Dehydrogenase gene in Timor Island people : A preliminary report (Faculty of Medicine Universitas Indonesia, 2001)
Glucose 6 phosphate dehydrogenase (G6PD) deficiency is common in malaria endemic region, however no molecular study has been performed on G6PD deficiency in Timor Island, Indonesia a malarial hyperendemic area which Proto Malay is the majority of the people in that island. To observe the frequency and molecular type of mutations in G6PD deficient Proto Malay people, 118 native people were screened using formazan ring test. Mutation in the G6PD gene were determined by MPTP (Multiple PCR using Multiple Tandem Forward Primers and a common Reserve Pimer) method and confirmed by automatic sequencer. This study shows that three males have lower G6PD activity. Using MPTP method, a point mutation could be indicated in the two cases. Sequencing of the amplified products in 2 G6PD patients disclosed mutations of T383C in exon 5 and C 592 T in exon 6 in respective case. Our result documents point mutations in exon 5 and exon 6 in the G6PD gene of two Proto Malay people in Timor. These mutations are common in Asia region. (Med J Indones 2001; 10: 210-3)